Macular sensitivity and morphology after intravitreal injection of triamcinolone acetonide for macular edema secondary to central retinal vein occlusion - Mimura T (Dove Medical Press, 2012)
Hidetaka Noma,1 Tatsuya Mimura21Department of Ophthalmology, Yachiyo Medical Center, Tokyo Women’s Medical University, Chiba, 2Department of Ophthalmology, Medical Center East, Tokyo Women’s Medical University, Tokyo, JapanAbstract: It has been reported that microperimetry is effective for evaluating macular function. The aim of this paper is to report and discuss changes seen in macular sensitivity and macular thickness after intravitreal injection of triamcinolone acetonide (IVTA) in two patients with macular edema and central retinal vein occlusion (CRVO). Two eyes from two patients with CRVO (one each with ischemic and nonischemic CRVO) received IVTA for macular edema. Microperimetry was performed to measure macular sensitivity within the central 4, 10, and 20 degree fields, while the macular thickness within these fields was measured by optical coherence tomography. The mean macular thickness and macular sensitivity within the central 4, 10, and 20 degree fields improved after IVTA in the patient with nonischemic CRVO. In contrast, the mean macular thickness and sensitivity within the central 4, 10, and 20 degree fields showed little change after IVTA in the patient with ischemic CRVO. IVTA improves macular sensitivity and morphology in nonischemic CRVO, so further evaluation of this treatment is justified.Keywords: central retinal vein occlusion, macular edema, triamcinolone acetonide, macular sensitivity